Monster tribe. 1 - Masui, Jyuu (Yen Press, 2025)
Ten is a high school boy who wants nothing more than an average, peaceful life, which is tough for a half-human from a family full of monsters. After a portal is torn open between the monster world and their own, Ten and his brothers are pressed to hunt down the invaders threatening humanity, with the promise that success means getting a wish granted. But can they safely see their mission through? And will Ten ever achieve the normal days he dreams of?